Molecular diversity of neurotoxins from Clostridium botulinum type D strains. - Moriishi, K (1989)
The molecular properties of Clostridium botulinum type D South African (D-SA) were compared with those of neurotoxins from type D strain 1873 (D-1873) and type C strains Stockholm and 6813. D-SA toxin, purified 610-fold from the culture supernatant in an overall yield of 30%, consisted of an intact peptide chain with a molecular weight of 140,000. Limited proteolysis of the toxin by trypsin formed a dichain structure consisting of a light chain (Mr, 50,000) and a heavy chain (Mr, 90,000) linked by a disulfide bond(s) and enhanced the lethal activity about fourfold. Antibodies against the D-SA toxin light chain reacted with D-1873 toxin but not with C1 toxins. On the other hand, antibodies against the heavy chain of D-SA toxin cross-reacted with type C strain Stockholm, D-1873, and type C strain 6813 toxins in that order. Amino-terminal sequences of heavy and light chains of D-SA and D-1873 toxins were similar but not identical. These results indicate that within the type D strains, neurotoxins differ in molecular structure and antigenicity.